Advances in Information and Computer Security 8th International Workshop on Security, IWSEC 2013, Okinawa, Japan, November 18-20, 2013, Proceedings - Sakiyama, Kazuo; Terada, Masayuki (Security and Cryptology, 2013)
This book constitutes the refereed proceedings of the 8th International Workshop on Security, IWSEC 2013, held in Okinawa, Japan, in November 2013. The 20 revised selected papers presented in this volume were carefully reviewed and selected from 63 submissions. They are organized in topical sections named: software and system security, cryptanalysis, privacy and cloud computing, public key cryptosystems, and security protocols.